Bichromatic particle streak velocimetry bPSV: interfacial, volumetric three-component velocimetry using a single camera - Voss, Björn Magnus; Stapf, Julian; Garbe, Christoph S. (Experiments in fluids, 2012)
We propose a novel technique for three-dimensional three-component (3D3C) interfacial flow measurement. It is based on the particle streak velocimetry principle. A relatively long integration time of the camera is used for capturing the movement of tracer particles as streaks on the sensor. The velocity along these streaks is extracted by periodically changing the illumination using a known pattern. A dye with different absorption characteristics in two distinct wavelengths is used to color the fluid. The depth of particles relative to the fluid interface can then be computed from their intensities when illuminated with light sources at those two different wavelengths. Hence, from our approach, a bichromatic, periodical illumination together with an image processing routine for precisely extracting particle streak features is used for measuring 3D3C fluid flow with a single camera. The technique is applied to measuring turbulent Rayleigh-Bénard convection at the free air--water interface. Using Lagrangian statistics, we are able to demonstrate a clear transition from the Batchelor regime to the Richardson regime, both of which were postulated for isotropic turbulence. The relative error of the velocity extraction of our new technique was found to be below 0.5 %.